Localization of objects using passive radio frequency identification technology - Cheng, Yew Jie. (2010)
Radio Frequency Identification (RFID) has been widely used in our daily life. Many commercial products ranging from system to scanner uses RFID. The usage of RFID can range from animal identification to inventory tracking to bus ride payment. Nowadays, most of the people will carry at least 1 RFID products around. RFID bus tags, which are used for the payment of bus rides, are products that had already been a part of parcel of human lives. Most countries had adopted the concept of bus concession using RFID tags. The demand for using RFID is on the rise. One of the main reasons for the increased demand is that information could be easily transfer from the RFID Reader and stored into the RFID Tags without worrying that the information would be lost. RFID provides not only accurate transmission of information, but also provides mobility for the users. This would encourage more applications to integrate with the RFID. Localization of an object (to detect the position) is not something new. Many technologies had been researched and implemented for the localization of objects. These technologies consist of Global Positioning System (GPS), Wi-Fi and Bluetooth technology. These technologies require purchasing of the equipments which may be expensive. Thus, an alternate way of localization is the usage of RFID technology. A handful of researches had been done on localization of RFID but most of the researches carried out were focused on the active tags, little attention was given to the passive tags. Passive tags are cheap and do not require any batteries for operation while the active tags requires the need of batteries. These advantages may attract more people to invest in localization of passive tags